The future of lithium availability for electric vehicle batteries - Speirs,J; Contestabile,M; Houari,Y; Gross,R (Renewable and Sustainable Energy Reviews, 2014)
Electric vehicles using lithium batteries could significantly reduce the emissions associated with road vehicle transport. However, the future availability of lithium is uncertain, and the feasibility of manufacturing lithium batteries at sufficient scale has been questioned. The levels of lithium demand growth implied by electric vehicle deployment scenarios is significant, particularly where scenarios are consistent with global GHG reduction targets. This paper examines the question of future lithium availability for the manufacturing of lithium batteries for electric vehicles.In this paper we first examine some of the existing literature in this area, highlighting the levels of future lithium demand previously considered and pointing to the variables that give rise to the range of outcomes in these assessments. We then investigate the ways in which lithium availability is calculated in the literature based on both lithium demand from electric vehicles and lithium supply from both brines and ore.This paper particularly focuses on the key variables needed to make an assessment of future lithium availability. On the demand side, these variables include future market size of electric vehicles, their average battery capacity and the material intensity of the batteries. The key supply variables include global reserve and resource estimates, forecast production and recyclability.We found that the literature informing assumptions regarding the key variables is characterised by significant uncertainty. This uncertainty gives rise to a wide range of estimates for the future demand for lithium based on scenarios consistent with as 50% reduction in global emissions by 2050 at between 184,000 and 989,000 t of lithium per year in 2050. However, lithium production is forecast to grow to between 75,000 and 110,000 t per year by 2020. Under this rate of production growth, it is plausible that lithium supply will meet increasing lithium demand over the coming decades to 2050.